Not for children’s ears? Parents’ insights into early childhood overweight and obesity treatment - My Sjunnestrand; Nicklas Neuman; Anna Ek; Karin Nordin; Ximena Ramos Salas; Kajsa Järvholm; Karin Eli; Paulina Nowicka (Scandinavian Journal of Primary Health Care, 2025)
This study offers novel insights into parents’ experiences of healthcare interactions during weight-related visits. Data were collected through the More and Less Europe study, a randomized controlled trial evaluating a parent support program for children (aged 2–6 years) with overweight or obesity in Sweden, Romania, and Spain to capture parents’ experiences of healthcare interactions. Semi-structured interviews were conducted with 45 Swedish parents (71% mothers, 60% with university degree, 51% of migrant background) of 45 children (mean age 7.1 years, SD 1.3, 76% girls) who received standard treatment for overweight or obesity. The interviews were analyzed thematically, identifying two themes: (1) Support or blame, with subthemes Validating family-centeredness, Overly generic advice, and Stigma and the sense of failing; (2) The place and role of the child, with subthemes Neutral, honest, and direct communication, Not for children’s ears, and Framing the message with care. While some parents described supportive interactions, others expressed disappointment with generic advice and inadequate support. Some recalled stigmatization, sometimes in the child’s presence, raising concerns about the child’s well-being. Approaches to preparing children for visits ranged from neutral to direct explanations. Parents expressed contrasting views on children’s presence during weight-related discussions: while some felt such discussions would harm their child, others supported children’s presence in open and age-appropriate discussion. This study fills a critical gap in obesity management communication by highlighting parental concerns about children’s exposure to weight-related discussions. Addressing these concerns is essential to reducing weight stigma in healthcare and protecting children from harmful experiences.